2008
DOI: 10.1002/dvg.20477
|View full text |Cite
|
Sign up to set email alerts
|

Chordate origins and evolution

Abstract: No abastract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…Of course “Phylogenetic speculation is expected of every study of Enteropneusta!” (Bullock, 1944) and speculations on the evolution of the chordate nervous system abound (Garstang, 1928; Nübler‐Jung and Arendt, 1996; Nielsen, 1999; Holland, 2003; Lacalli, 2006, 2008, 2010). Most of the recent publications discuss modern molecular ontogenetic data in the light of the latest phylogenetic tree based on molecular data (Holland, 2003; Brown et al, 2008; Swalla and Xavier‐Neto, 2008; Holland, 2009; Nomaksteinsky et al, 2009). In our view, this practice ignores the wealth of information that is present in comparative data on any other level, although some authors have shown that, e.g., phylogenetic information content on morphological levels is generally higher than in sequence data (Giribet, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Of course “Phylogenetic speculation is expected of every study of Enteropneusta!” (Bullock, 1944) and speculations on the evolution of the chordate nervous system abound (Garstang, 1928; Nübler‐Jung and Arendt, 1996; Nielsen, 1999; Holland, 2003; Lacalli, 2006, 2008, 2010). Most of the recent publications discuss modern molecular ontogenetic data in the light of the latest phylogenetic tree based on molecular data (Holland, 2003; Brown et al, 2008; Swalla and Xavier‐Neto, 2008; Holland, 2009; Nomaksteinsky et al, 2009). In our view, this practice ignores the wealth of information that is present in comparative data on any other level, although some authors have shown that, e.g., phylogenetic information content on morphological levels is generally higher than in sequence data (Giribet, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It appears less likely that a metameric organization around a well-developed CNS of ancient metazoans devolved to form the partially centralized epithelial nerve nets found in diploblasts (Matus, et al, 2007b, Satterlie, 2011) and the simple CNS found in some basal bilaterians (Brown, et al, 2008, Fritzsch and Glover, 2006, Harzsch and Muller, 2007, Raikova, et al, 2000). A non-metamerically organized nervous system with no specialized sensory organs seems to be the most parsimonious assumption for diploblasts and, by logical extension, bilaterian ancestors (Bourlat, et al, 2006, Budd, 2001, Satoh, 2008, Swalla and Xavier-Neto, 2008). The different patterns of nervous system of extant deuterostomes are considered here to be independently derived from such bilaterian ancestors, reflecting either independent formation of a CNS (acorn worms, cephalochordates, urochordates, vertebrates) or show a transformation into a pentameric nerve net (echinoderms).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding chordate origins and evolution has been a preeminent challenge for biologists over the last two centuries (Swalla and Xavier-Neto 2008). The phylum Chordata consists of three distinct lineages: cephalochordates (lancelets), tunicates or urochordates (sea squirts, salps and appendicularians) and craniates (i.e., cyclostomes and vertebrates).…”
Section: Introductionmentioning
confidence: 99%